Signification of autogenous skintransplantation in purulent surgery - K. V. Lipatov; E. A. Komarova (Трансплантология (Москва))
Split-skin grafting is one of the most accepted and significant operations in the purulent surgery. In this study we appraised effectiveness and possibilitys of this method of dermepenthesis and discuss about speciality of split-skin grafting use in the purulent surgery.